Membrane Lipid-KIR2.x Channel Interactions Enable Hemodynamic Sensing in Cerebral Arteries. Issue 6 (June 2019) - Sancho, Maria; Fabris, Sergio; Hald, Bjorn O.; Brett, Suzanne E.; Sandow, Shaun L.; Poepping, Tamie L.; Welsh, Donald G.
Abstract : Objective—: Inward rectifying K + (KIR ) channels are present in cerebral arterial smooth muscle and endothelial cells, a tandem arrangement suggestive of a dynamic yet undiscovered role for this channel. This study defined whether distinct pools of cerebral arterial KIR channels were uniquely modulated by membrane lipids and hemodynamic stimuli. Approach and Results—: A Ba 2+ -sensitive KIR current was isolated in smooth muscle and endothelial cells of rat cerebral arteries; molecular analyses subsequently confirmed KIR 2.1/KIR 2.2 mRNA and protein expression in both cells. Patch-clamp electrophysiology next demonstrated that each population of KIR channels was sensitive to key membrane lipids and hemodynamic stimuli. In this regard, endothelial KIR was sensitive to phosphatidylinositol 4, 5-bisphosphate content, with depletion impairing the ability of laminar shear stress to activate this channel pool. In contrast, smooth muscle KIR was sensitive to membrane cholesterol content, with sequestration blocking the ability of pressure to inhibit channel activity. The idea that membrane lipids help confer shear stress and pressure sensitivity of KIR channels was confirmed in intact arteries using myography. Virtual models integrating structural/electrical observations reconceptualized KIR as a dynamic regulator of membrane potential working in concert with other currents to set basal tone across a range of shear stresses and intravascular pressures. Conclusions—: The data show for the first time that specific membrane lipid-KIR interactions enable unique channel populations to sense hemodynamic stimuli and drive vasomotor responses to set basal perfusion in the cerebral circulation. Abstract : Supplemental Digital Content is available in the text.